EFEKTIVITAS IMPLEMENTASI REALISASI PAJAK DAERAH DENGAN SISTEM PEMBAYARAN DIGITAL PADA BPKPAD KABUPATEN TEMANGGUNG TAHUN 2023-2024 - Ana Aulia; Siti Afidatul Khotijah (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
BPKPAD is a local government institution that has an important role in financial management at the district or city level. Digital payments have become an increasingly popular trend in recent years. Local governments have also begun to adopt digital payments as one way to improve the efficiency and effectiveness of collecting local tax realization. This study aims to determine the effectiveness of the implementation of local tax realization with a digital payment system at BPKPAD Temanggung Regency. This research uses secondary data analysis method obtained from BPKPAD Temanggung Regency. The data used is data on local tax revenue from 2023 and 2024. The results showed that digital payments have been implemented and increased the realization of local taxes at BPKPAD Temanggung Regency. The percentage of non-cash (digital) payments increased from 34% in 2023 to 43.30% in 2024.